Impact of information technology on strategic management in the banking sector of Iraq - Adetayo Olaniyi Adeniran; Hamid Mohsin Jadah; Noor Hashim Mohammed (Insights into Regional Development)
The main objective of the study is to examine the impact of information technology on strategic management in the banking sector. The specific objectives are to identify the applications of information technology in banking sector; to examine the association between education level and customer’s usage of IT applications in the banking sector; and to examine the relationship between information technology and organization’s strategy. The methodology of the study is supported by interview of bank customers and interview of industry experts based on purposive sampling technique. The findings revealed that Electronic cards, ATMs, online banking, electronic payment, and mobile banking were the major application of IT in Iraq banking sector. There is an association between education level of bank customers and their usage of IT applications regarding banking transactions in Iraq. There is a relationship between information technology and organization’s strategy which has resulted in value creation and competitive advantage of banks. It was recommended that for better performance of IT on banking, the management of banking sector should adopt better policies that will encourage users to adopt IT usage in banks. The main contribution of this study is that information technology enhances value creation and competitive advantage in Iraq banks.